Correlation Between Outpatient Preliminary Diagnosis of Venous Insufficiency and Venous Doppler Ultrasound Findings: A Retrospective Cohort Study - Atilla Orhan (Genel Tıp Dergisi)
Background: This retrospective cohort study delves into the correlation between outpatient preliminary diagnoses of venous insufficiency and venous Doppler ultrasound findings. Methods: Conducted at our hospital from 01.0102018 to 31.12.2018, the study scrutinized patient records to gauge the concordance between clinical diagnoses and Doppler ultrasound results. Results: Among the 92 patients included in the analysis, Doppler ultrasound confirmed venous insufficiency diagnoses in 46.74% of cases. More than half of the patients who were initially suspected to have venous insufficiency had normal radiological findings. This suggests that during outpatient treatments, physical examination may not be given enough consideration due to the high number of patients. Moreover, it can be a time-consuming and labor-intensive process. Furthermore, our findings suggest that there is a strong correlation between venous reflux in a lower extremity vein and its impact on adjacent veins. Conclusions: The study highlights the crucial importance of Doppler ultrasonography in improving diagnostic precision, particularly for patients who have not undergone a thorough physical examination in the outpatient clinic. The study also finds that changes in flow due to venous insufficiency primarily affect adjacent veins.